Velocity shift of Mg ii and Al iii broad absorption lines in quasar SDSS J134444.33+315007.6. (23rd September 2020) - Lu, Wei-Jian; Lin, Ying-Ru
ABSTRACT: We report, for the first time, a synchronized velocity shift of Mg ii and Al iii broad absorption lines (BALs) in quasar SDSS J134444.33+315007.6 (hereafter, J1344+3150). We found this quasar from a sample of 134 Mg ii BAL quasars with multi-epoch observations. This quasar contains three low-ionization BAL systems, the fastest of which at -17 000 km s^-1 shows a kinematic shift of -1101 and -1170 km s^-1 in its Mg ii and Al iii ions, respectively, during a rest-frame time of about 3.21 yr. Meanwhile, this quasar also shows other various variation characteristics, including an obvious weakening in its continuum, a coordinated enhancement in multiple emission lines (Mg ii, C iii, and Al iii ), and a coordinated enhancement in three Al iii absorption troughs. These variation characteristics convincingly indicate that the BAL outflows of J1344+3150 are under the influence from the background radiation energy. Thus, we infer that the velocity shift displayed in system A in the quasar J1344+3150 may indicate an actual line-of-sight acceleration of an outflow due to the radiation pressure from the central source.